Malignant Catarrhal Fever of Cattle Is Associated with Low Abundance of IL-2 Transcript and a Predominantly Latent Profile of Ovine Herpesvirus 2 Gene Expression - Meier-Trummer, Claudia S; Rehrauer, Hubert; Franchini, Marco; Patrignani, Andrea; Wagner, Ulrich; Ackermann, Mathias (PloS one, 2009)
Background: Malignant catarrhal fever (MCF) is a lethal disease of cattle, characterized by vasculitis, necrosis, and accumulation of activated, dysregulated cytotoxic lymphocytes in various tissues. Ovine gamma herpesvirus 2 (OvHV-2) is a causative agent of MCF, which may trigger the disease through immunopathogenic pathways. Lymphocytes are the main target of the virus. However, the pathogenic basis of the disease is still mysterious. Methods/Findings: We hypothesized that the gene expression patterns of OvHV-2 and the relative abundances of host cell transcripts in lymphnodes may be used to identify pathways that help to explain the pathogenesis of MCF. Therefore, viral and host cell gene expression patterns in lymph nodes of animals with MCF and healthy controls were analyzed by microarray. Two regions on the viral genome were transcriptionally active, one encoding an orthologue to the latency-associated nuclear antigen (ORF73) of other gamma herpesviruses, the other with no predicted open reading frame. A vast number of transcripts related to inflammatory processes, lymphocyte activation, cell proliferation and apoptosis were detected at different abundances. However, the IL-2 transcript was eminent among the transcripts, which were, compared to healthy controls, less abundant in animals with MCF. The ratio between CD4- and CD8-positive T-lymphocytes was decreased in the lymphnodes of animals with MCF compared to healthy controls. In contrast, the same ratio was stable, when peripheral blood lymphocytes were analyzed. Conclusions/Significance: The phenotype of mice with a deficient IL-2-system almost perfectly matches the clinical signs observed in cattle with MCF, which feature a significantly decreased IL-2 transcript abundance, compared to healthy cattle. This supports the hypothesis that immunopathogenic events are linked to the pathogenesis of MCF. IL-2-deficiency may play an important role in the process. Therefore, this work opens new avenues for research on MCF.